2014
DOI: 10.1124/jpet.113.212613
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan Induces a Prolonged Proangiogenic Effect and Augments Endothelium-Mediated Neuroprotection after Oxygen and Glucose Deprivation: Role of Vascular Endothelial Growth Factors A and B

Abstract: Angiogenesis is a key component of recovery after stroke. Angiotensin II receptor blocker (ARB) treatment improves neurobehavioral outcome and is associated with enhanced angiogenesis after stroke. The purpose of this study is to investigate the temporal pattern of the ARB proangiogenic effect in the ischemic brain and its association with vascular endothelial growth factors VEGF-A and VEGF-B. Wistar rats were exposed to 90-minute middle cerebral artery occlusion and treated with candesartan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 59 publications
3
35
0
2
Order By: Relevance
“…Interestingly, the AT2 agonist (CGP-121141A) had no significant effect on VEGF expression in either PC3 or DU145 cells, thus ruling out the role of AT2 receptor stimulation in candesartanmediated inhibition of VEGF expression. Our previous studies in a stroke model indicated increased VEGF expression by candesartan (Guan et al, 2011), probably through endothelial cells (Alhusban et al, 2013;Soliman et al, 2014); in the current model, where angiogenesis is mainly driven by the tumor cells, the mechanism leading to inhibition of VEGF expression is not via AT2 stimulation. As reviewed previously, the effects of ARBs on angiogenesis are dose-, tissue-, and context-dependent (Willis et al, 2011) Since no significant changes in survival pathways and tumor cell function with the clinical concentrations of candesartan were observed in the in vitro experiments, we wanted to rule out that the decrease in VEGF expression in candesartan-treated tumors is due to the paracrine effect from prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the AT2 agonist (CGP-121141A) had no significant effect on VEGF expression in either PC3 or DU145 cells, thus ruling out the role of AT2 receptor stimulation in candesartanmediated inhibition of VEGF expression. Our previous studies in a stroke model indicated increased VEGF expression by candesartan (Guan et al, 2011), probably through endothelial cells (Alhusban et al, 2013;Soliman et al, 2014); in the current model, where angiogenesis is mainly driven by the tumor cells, the mechanism leading to inhibition of VEGF expression is not via AT2 stimulation. As reviewed previously, the effects of ARBs on angiogenesis are dose-, tissue-, and context-dependent (Willis et al, 2011) Since no significant changes in survival pathways and tumor cell function with the clinical concentrations of candesartan were observed in the in vitro experiments, we wanted to rule out that the decrease in VEGF expression in candesartan-treated tumors is due to the paracrine effect from prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Из всех сартанов наибольшие церебропротективные эффекты продемонстрировал кандесартан, в т. ч. в исследованиях ACCESS (Acute Candesartan Cilexetil Evaluation in Stroke Survivors) и SCOPE (Study on Cognition and Prognosis in the Elderly) [25,26].…”
Section: в настоящее время по результатам многочисленных исследованийunclassified
“…Так, было пока-зано, что низкие дозы кандесартана, не снижающие АД, способны предотвращать МИ у гипертензивных крыс, а также были продемонстрированы преимущества канде-сартана, несмотря на его гидрофильность, перед другими БРА при проникновении через гематоэнцефалический барьер, что позволяет этому препарату снижать невроло-гический дефицит и уменьшать размер очага инсульта [25]. Экспериментально было доказано, что кандесартан обеспечивает длительный ангиогенный эффект, что, по мнению ряда авторов, играет определяющую роль в нейро восстановительном процессе после инсульта, т. к. способствует нейрогенезу и синапсогенезу [26].…”
Section: в настоящее время по результатам многочисленных исследованийunclassified
“…In the ischemic stroke model, the pro-angiogenic response of candesartan was associated with vascular protection and reduced blood brain barrier permeability in the brain and suggested that candesartan mediates reparative angiogenesis resulting in improved functional outcome [13] . This preservation of barrier function despite the increase of the vascular permeability factor, VEGF-A, was attributed to the simultaneous upregulation of angiopoietin-1, which mediates new blood vessel stabilization and maturation through pericyte recruitment [14] . We and others have also shown increased vascular density and neuroprotection in vivo with losartan and valsartan pretreatment suggesting a class effect of ARBs [15, 16] .…”
Section: Arbs Contribute To Initiation and Stabilization Of New Bloodmentioning
confidence: 99%
“…Over the past decade, we have shown that post-stroke treatment with ARBs and in particular with candesartan, resulted in vascular protection and was positively associated with a proangiogenic state [12-14, 19-21] . Our work clearly identified that the ARB-enhanced proangiogenic state coincided with increased brain levels of the pro-angiogenic factors: brain derived neurotrophic factor (BDNF) and VEGF isoforms; VEGF-A and B.…”
Section: Arbs Increase Proangiogenic State Via Expression Of Angiogenmentioning
confidence: 99%